Synthesis, characterization and in vitro bioactivity studies of isoindolin‐1‐3‐phosophonate compounds. (17th January 2022) - Jelali, Hamida; Al Nasr, Ibrahim S.; Koko, Waleed S.; Khan, Tariq A.; Deniau, Eric; Sauthier, Mathieu; Alresheedi, Faisal; Hamdi, Naceur
Abstract: In this work, efficient synthesis of isoindolin‐1‐one‐3‐phosphonates under catalyst‐ and solvent‐free conditions was reported to afford the desired compounds in excellent yields with potent pharmacological properties. The synthesis method involves the preparation of isoindolin‐1‐one‐3‐phosphonates by a "one‐pot" three‐component reaction of 2‐formylbenzoic acid with primary amines and dimethyl phosphite under solvent‐ and catalyst‐free conditions. All new compounds were characterized by 1 H NMR, 13 C NMR, FT‐IR and elemental analysis techniques. The compounds were investigated for their bioactivities against a group of microorganisms, Leishmania major, Toxoplasma gondii parasites, and the DA‐MB‐231 and MCF‐7 cancer cell lines in vitro. Compound 4a was found to be the most active against L. M. luteus, L. monocytogenes and C. albicans microorganisms, with inhibition zones of 35, 22 and 38 mm, respectively. The compounds were also investigated for their antiparasitic activities, and compounds 4a and 4b were the most active against L. major amastigotes and promastigotes with EC50  < 1 μM. All tested compounds had potent anticancer activity against the MDA‐MB‐231 and MCF‐7 human cell lines with EC50  < 1.5 μM. Compounds 4a and 4b are good drug candidates for antimicrobial, antileishmanial and anticancer drug discovery, and further in vivo studies are highly recommended prior to any clinical trials. Abstract :